P31 Engaging with stakeholders to inform the development of a computer model for the NHS health check programme: workHORSE project. (September 2018) - Hyseni, L; Guzman-Castillo, M; Kypridemos, C; Collins, B; Schwaller, E; Capewell, C; Boland, A; Dickson, R; O'Flaherty, M; Lloyd-Williams, F
Abstract : Background: The NHS Health Check Programme (NHSHCP) is a multifactorial 'risk-reduction' programme offered to all adults in England aged 40–74. Studies of the NHSHCP suggest that it might be further improved by including additional conditions and by facilitating local commissioning. This project aims to use stakeholder engagement to co-produce and develop a validated open-source/open access, flexible decision support tool to enable local commissioners to quantify the local effectiveness, cost-effectiveness and equity of the NHSHCP. Methods: We have adopted the innovative approach of engaging with key stakeholders in four iterative workshops, to co-produce model and scenario specifications. We identified stakeholders using our extensive networks and using the snowballing techniques. In workshop 1, we used the validated Hovmand 'group model building' approach to engage stakeholders in a series of pre-piloted, structured, small group exercises. Our key objectives were to 1) facilitate engagement of stakeholders and modelling teams, 2) develop a shared understanding of the current implementations of the NHSHCP, 3) identify what is working well and less well, 4) identify future hopes for the NHSHCP, and 5) explore features and specifications to potentially include in a useful decision-support tool for stakeholders. Results: Fifteen key stakeholders participated in workshop 1. They spanned all levels: local (NHS commissioners, GPs, academics), third sector organisations and national organisations (including PHE and NICE). This diverse mix of stakeholders provided a rich diversity of perspectives. Stakeholders agreed that there is continued (financial and political) support for the NHSHCP. However, many stakeholders highlighted issues with the lack of data on processes and outcomes, variety in quality of delivery and suboptimal public engagement. Stakeholders' hopes for the programme included maximising coverage, uptake and appropriate referrals, and producing additional evidence on population health, equity and economic impacts. Stakeholders suggested several useful features including focusing on feasible NHSHCP implementations based on good-practice template scenarios, analysis of broader prevention activities at local level, accessible local data, broader economic perspectives and fit-for-purpose outputs. These results then informed the objectives for the second and subsequent project workshops, which will include sharing and refining a prototype user interface, and exploring different scenarios to be evaluated. Conclusion: This project includes innovative approaches to engage with key stakeholders via Hovmand style workshops. These potentially offer an effective participatory method for involving stakeholders in the process of understanding a complex problem, and collaborating in the joint development of a decision-support tool focused on the needs of the final users.